Procedural Restrictions on Money Laundering Investigation in the Tax Sector under the Regime of Law Number 20 of 2025 - Agussalim A. Gadjong (CV. Social Politic Genius (SIGn), 2025)
This research analyzes the implications of the enactment of coercive measure procedural restrictions on the independence of the DGT Investigator under the regime of Law Number 20 of 2025. This normative-doctrinal legal research employs a statute and conceptual approach to evaluate retrospective performance for the 2020 to 2024 period and project the impact of the new Law post-January 2, 2026. The research results indicate that the decline in historical case dossier settlement rates was purely caused by internal technical-cyber constraints, rather than a normative authority weakness. However, the new Criminal Procedure Code unification fundamentally degrades sectoral independence through the revocation of independent arrest and detention authority, centralized Police subordination triggering structural transactional risks, and an absolute competence dispute with the Attorney General’s Office that contradicts the ultimum remedium principle. To overcome this procedural stagnation, the DGT formulated an administrative bypass strategy. This tactic shifts the law enforcement focus to the non-coercive Preliminary Evidence Examination phase through the exploitation of forensic digital evidence and the independent exchange of international beneficial owner information. This research recommends legislative reconstruction to restore equal horizontal institutional relations, affirm absolute competence boundaries, expand the non-conviction-based confiscation mechanism, and accelerate the establishment of specialized tax cyber units in regional areas to guarantee national fiscal resilience.